Eksplorasi Etnomatematika Terhadap Alat Musik Taganing, Makanan Putu Bambu, Dan Permainan Gasing - Aritonang, Arista; Marbun, Valentina Margaretha; Simangunsong, Sarah; Marpaung, Shelly; Lumban Gaol, Gerardus; Sinaga, Oriza (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2025)
This study aims to explore mathematical concepts embedded in local cultural practices through an ethnomathematical approach, focusing on the traditional game Gasing, the traditional musical instrument Taganing, and the traditional food Putu Bambu. These three cultural objects were analyzed to identify mathematical elements such as geometry, symmetry, three-dimensional shapes, similarity, number patterns, and measurement within the context of discrete mathematics. The research employed a qualitative observational method and literature review using an ethnographic approach. The findings reveal that Taganing incorporates concepts of plane and solid geometry, as well as tonal regularity that can be mathematically mapped; Gasing involves rotational motion, cylindrical shapes, and discrete calculations such as the number of spins and spinning duration; while Putu Bambu reflects cylindrical geometry and the relationship between circles and rectangles in its packaging and presentation. These results demonstrate that local cultural heritage can serve as an effective source of contextual learning to enhance students' mathematical understanding and simultaneously support the preservation of cultural values in education.  Keywords: ethnomathematics, local culture, Taganing, Gasing, Putu Bambu, contextual learning